Bile acids: potential links to overweight/obesity and androgen levels in pubertal girls - Malave-Ortiz, Sofia; McNeley, Samantha A. M.; Denslow, Sheri; Lih, Fred B.; Shaw, Natalie D. (Frontiers in Endocrinology, 2025)
BackgroundPubertal girls with higher body mass index (BMI) or total body fat (TBF) have higher androgens. We demonstrated that several bile acids (BAs) were associated with BMI, TBF, and androstenedione in an untargeted metabolomics study.ObjectiveTo investigate the relationship between body composition, BAs, and androgens in pubertal girls.MethodsBlood samples were collected at up to seven study visits that included Tanner staging, breast ultrasound, and dual-energy x-ray absorptiometry. Serum total testosterone, free testosterone (FT), androstenedione, dehydroepiandrosterone sulfate, and 18 BAs were measured by liquid chromatography mass spectrometry. Generalized estimating equations estimated associations between TBF percent or BMI z-score, hormones, and BAs adjusted for time since enrollment, age, menarche status, race, and breast morphological stage. Exposures were taken from the preceding study visit (lagged).ResultsEighty-two participants (aged 10.9 ± 1.4 SD years; 55% non-Hispanic White, 29% non-Hispanic Black, 11% Hispanic, 6% Other; 65% normal weight, 35% overweight/obese) contributed an average of 2.59 samples. BAs were stable over time and not associated with menarchal status. BMI and TBF were negatively associated with total BAs (pFDR = 0.0001). FT was nominally positively associated with two primary, conjugated BAs: taurocholic acid (p = 0.047) and taurodeoxycholic acid (p = 0.036).ConclusionBAs are important signaling molecules with roles in metabolic and endocrine function. BMI and TBF were inversely associated with BAs, and two BAs were nominally positively associated with FT in girls across a spectrum of body weights. These results suggest novel biological links between altered BA signaling, overweight/obesity, and androgen production among pubertal girls.